Effectsof Self-Management Promotion Program Using LINE Application on Health Behaviors and A1C Levels among Uncontrolled Diabetes Patients - boontanapisan, netnapa; Naewbood, Supaporn; Tipwareerom, Worawan (NU Journal of Nursing and Health Sciences, 2022)
The purpose of this quasi-experiment research was to study the effects of self-management promotion program using LINE application on health behaviors and A1C levels in uncontrolled diabetes patients. The samples were 60 type 2 uncontrolled diabetes mellitus patients. The 30 participants of the experimental group received the self-management promotion program for 12 weeks, which was developed by the researcher based on the self-management concept of Kanfer and Gaelick-Buys while the 30 participants of the control group received conventional nursing care. Research tools consisted of the self-management promotion program and a questionnaire on health behaviors. The research tools were content validated by five experts with Content Validity Index of 0.80 and Cronbach’s alpha coefficient at 0.80. Data were analyzed by using frequency, percentage, mean, standard deviation, paired t-test and independent t-test. The results were that the mean scores of health behaviors in the experimental group were significantly higher than before intervention and also higher than the control group. The mean level A1C was lower than before the program and those control group with significant at p<.001. This results can promote the effects of self-management promotion program using LINE application which modified health behaviors and decreased A1C levels of type 2 uncontrolled diabetes patients.